An Analysis of Students’ Vocabulary Mastery in Using Antonym of Second Grade Students in SMP Swasta Advent 5 Medan - Sahlan Tampubolon; Nurhayati Sitorus; Ririn Krisniati Panjaitan (Merwin Publisher, 2023)
In this study, descriptive analysis was used as the method which focused on describing the students’ vocabulary mastery in using antonym. The data was taken from 25 students of the 2nd grade in SMP Swasta Advent 5 Medan. The study used content analysis as the instrument of collecting data. The result of this study shows that the level ability of students’ vocabulary mastery in using defining antonym was categorized as poor level. The percentage of the level ability of students’ vocabulary mastery in doing the antonym test shows that from 25 samples, there were 3/12 % students fall in the excellent level, 2/8 % students fall in the good level, 3/12 % students fall in the fair level, 6/24 % students fall in weak level, 11/44 % students fall in poor level which can be concluded as the most level reached by the students. The graphic clearly shows that most of the students’ vocabulary mastery fall in the poor level in using antonym. The result of students’ interview which involved 5 participants which aimed to find out the students’ difficulties in learning vocabulary shows that most of students reciprocally mention that English is one of the most difficult subjects learnt at school. The lack of repetition by students was also one of the main reason of students limited vocabularies which lead to the result of poor level ability of students’ vocabulary mastery particularly in defining antonym. Keywords: descriptive analysis, vocabulary, antonyms